2022
DOI: 10.1039/d1tb02693c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sialic acid conjugates of the clinical near-infrared dye as next-generation theranostics for cancer phototherapy

Abstract: Cancer is a multifaceted global health problem that requires continuous action to develop next-generation cancer theranostics. Inspired by the emerging use of indocyanine green (ICG), the only clinical approved near-infrared...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Due to the weak blue fluorescence emitted by CPT, it is very challenging to study the organ distribution of CPT-ss-Sia by in vivo fluorescence imaging or tissue section imaging. Encouragingly, our previous research has found that modifying Sia with multiple substituents, including FITC, 30 CS, 31 ICG, 32 and DNP, 29 through the C9 position of Sia yields Sia derivatives that can effectively target tumors. Due to the high demand for Sia for tumor growth, tumor cells can efficiently take up Sia derivatives, including CPT-ss-Sia .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the weak blue fluorescence emitted by CPT, it is very challenging to study the organ distribution of CPT-ss-Sia by in vivo fluorescence imaging or tissue section imaging. Encouragingly, our previous research has found that modifying Sia with multiple substituents, including FITC, 30 CS, 31 ICG, 32 and DNP, 29 through the C9 position of Sia yields Sia derivatives that can effectively target tumors. Due to the high demand for Sia for tumor growth, tumor cells can efficiently take up Sia derivatives, including CPT-ss-Sia .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies observed a marked propensity of tumors to take up Sia derivatives bearing hapten or fluorochrome at the C9 position of Sia, including 2,4-dinitrophenylated Sia (DNP-Sia), 29 fluorescein isothiocyanate (FITC)-conjugated Sia (FITC-Sia), 30 the Changsha (CS) NIR dye conjugate of Sia (CS-Sia), 31 and the indocyanine green conjugate of Sia (ICG-Sia). 32 Notably, these Sia derivatives can be efficiently taken up by tumor cells and metabolically incorporated into cellular glycans, 33,34 leading to enhanced tumor accumulation and prolonged tumor retention. This is a plausible mechanism by which Sia derivatives target tumors.…”
Section: Introductionmentioning
confidence: 99%
“…1a), highlighting the importance of covalently linked ICG to PSMA NPs. Given that the Sia modification facilitates tumor targeting, 30,[32][33][34][35][36] Sia-PSMA-ICG NPs were also prepared; these NPs showed enhanced tumor targeting and photothermal therapy (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
“…1 These alarming data urgently require the development of effective cancer treatments. Commonly used cancer treatment methods include chemotherapy, 2,3 radiotherapy, 4 phototherapy, [5][6][7] and immunotherapy, [8][9][10][11] of which immunotherapy is attractive because it can call on the immune system to ght cancer cells. As a promising modality of cancer immunotherapy, vaccine immunization can provide long-term protection to the host with few side effects.…”
mentioning
confidence: 99%